PETCAM-A power Efficient TCAM for forwarding tables - Mishra, T.; Sahni, S. (2009 IEEE Symposium on Computers and Communications, 2009)
We investigate various TCAM architectures recently proposed for TCAM power and memory reduction and show that far better power and memory performance is possible when we use an optimal prefix set for the given routing table than when the original prefix set or the reduced prefix set as proposed in other work is used. For EaseCam, our experiments show a power and TCAM memory reduction of 96% to 98% and 62% to 69% respectively. For the suffix node architecture of, we get a power and TCAM memory reduction of 16% to 25% and 45% to 78% respectively.